A case report of misdiagnosed fetal lung mass and review of the literature - Wang, Zongyu; Xu, Chang; He, Taozhen; Yuan, Miao (Frontiers in pediatrics, 2023)
The patient was a male neonate, and a prenatal ultrasound had detected a right lung mass. He was born at term and after delivery had tachypnea and feeding difficulties. A chest x-ray and a computed tomography (CT) scan revealed a large mass in the right chest with compression on the right lung after birth. We initially considered congenital pulmonary airway malformation (CPAM). After conservative treatment, his respiratory symptoms worsened gradually, and he required continuous supplemental oxygen. The symptoms could not be relieved by puncturing due to a postnatal ultrasound having shown a mass with anechoic microcystic spaces. He therefore underwent an emergency thoracotomy and lobectomy at 14 days of age. The pathology was consistent with fetal lung interstitial tumor (FLIT). The patient remained healthy at the three-month follow-up. We reviewed the literature on FLIT and found that, to date, 23 cases have been reported worldwide.